2018
DOI: 10.5539/jmsr.v7n2p26
|View full text |Cite
|
Sign up to set email alerts
|

Modeling, Simulation and Optimization of Piezoelectric Bimorph Transducer for Broadband Vibration Energy Harvesting in Multi-Beam and Trapezoidal Approach

Abstract: The objective of the research is to design a broadband energy harvester device through the multi-beam approach and non-linear trapezoidal geometry approach. The performance of the composite piezoelectric PZT-PZN polycrystalline ceramic material is simulated using COMSOL Multiphysics, and results are compared using series configuration of a composite bimorph energy harvester which vibrates at its 1st fundamental frequency. We chose a five cantilever multibeam harvester to demonstrate that individual fundamental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 11 publications
1
8
0
Order By: Relevance
“…It is shown that increasing the width W 2 (at free end) lowers the resonance frequency, which agrees with our results. It was also shown that the trapezoidal shape generates higher voltage compared to the simple rectangular cantilever beam bimorph which matches our findings in previous works [6,12]. In this paper, we explore a unique design of 2-piece trapezoidal shaped piezoelectric bimorph to understand its effects on harvested power, power density, and bandwidth.…”
Section: Introductionsupporting
confidence: 88%
See 4 more Smart Citations
“…It is shown that increasing the width W 2 (at free end) lowers the resonance frequency, which agrees with our results. It was also shown that the trapezoidal shape generates higher voltage compared to the simple rectangular cantilever beam bimorph which matches our findings in previous works [6,12]. In this paper, we explore a unique design of 2-piece trapezoidal shaped piezoelectric bimorph to understand its effects on harvested power, power density, and bandwidth.…”
Section: Introductionsupporting
confidence: 88%
“…Equation (30) is substituted into equation (26). erefore, equation (26) can be rewritten to the integral formula in 6 Advances in Materials Science and Engineering equation 31, where w 1 is the shorter width of the bimorph and w 2 is the longer width of the bimorph:…”
Section: Qualitymentioning
confidence: 99%
See 3 more Smart Citations